An improved ghost-cell sharp interface immersed boundary method with direct forcing for particle laden flows. (15th October 2018) - Maitri, R.V.; Das, S.; Kuipers, J.A.M.; Padding, J.T.; Peters, E.A.J.F.
Highlights: An accurate and a stable sharp interface IBM is presented for DNS of particle laden flows. Torque computation on a particle is improved by exactly computing projected areas. Current ghost-cell IBM does not show spurious oscillations in pressure force. Present IBM is validated for relevant test cases of single and multi-particle systems. Abstract: In this paper, an accurate and stable sharp interface immersed boundary method(IBM) is presented for the direct numerical simulation of particle laden flows. The current IBM method is based on the direct-forcing method by incorporating the ghost-cell approach implicitly. An important feature of this IBM is the sharp representation of the solid surface, contrary to other variants of IBM for freely moving particles in which the solid surface is diffuse. Moreover, a correction of the diameter is not necessary for obtaining accurate results. The current ghost-cell IBM is stable because spurious oscillations incurred due to discontinuity in the pressure and velocity field in moving particle simulations is avoided. An algorithm for accurate torque computation is developed. The proposed algorithm is verified by comparison to an analytical expression and is shown to give a substantial improvement over the existing method. Finally, the present IBM is validated for various test cases of single and multi-particle systems and is shown to be accurate and robust for a wide range of flow conditions.